Unborn in the USA [videorecording (DVD)] - Fell, Stephen; Thompson, Will (First Run Features, 2007)
Provides a look into the secrets and deep pockets of the pro-life movement. Traveling across 35 states, the filmmakers are granted unprecedented access to pro-life groups, movement icons, fund-raising machines, and much more.